16q24.3 Microduplication in a Patient With Developmental Delay, Intellectual Disability, Short Stature, and Nonspecific Dysmorphic Features: Case Report and Review of the Literature - Bucerzan, Simona; Miclea, Diana; Lazea, Cecilia; Asavoaie, Carmen; Kulcsar, Andrea; Grigorescu-Sido, Paula (Frontiers in Pediatrics, 2020)
We describe the case of a seven-year-old female patient who presented in our service with severe developmental delay, intellectual disability, facial dysmorphism and femur fracture, observed in the context of very low bone mineral density. Array-based single nucleotide polymorphism (SNP array) analysis identified a 113 kb duplication involving the morbid OMIM genes: ANKRD11 (exon1), RPL13 and PGN genes. ANKRD11 deletions are frequently described in association with KBG syndrome, the duplications being less frequent (one case described before). The exome sequencing was negative for pathogenic variants or of uncertain significance in genes possibly associated with this phenotype. The patient presented subtle signs of KBG syndrome. It is known that the phenotype of KBG syndrome has a wide clinical spectrum, this syndrome being often underdiagnosed due to overlapping features with other conditions, also characterised by multiple congenital anomalies and intellectual disability. The particularity of this case is represented by the very low bone mineral density in a patient with 16q24.3 duplication. ANKRD11 haploinsufficiency is known to be associated with skeletal involvement, such as short stature, or delayed bone age. An effect on bone density has been observed only in experimental studies on mice with induced missense mutations in the ANKRD11 gene. This CNV also involved the duplication of the very conserved RPL13 gene, which could have a role for the skeletal phenotype of this patient, knowing the high level of gene expression in bone tissue and also the association with spondyloepimetaphyseal dysplasia Isidor Toutain type, in case of splicing mutations.